Reprogramming viral immune evasion for a rational design of next-generation vaccines for RNA viruses - Su, Chia-Ming; Du, Yijun; Rowland, Raymond R. R.; Wang, Qiuhong; Yoo, Dongwan (Frontiers in Immunology, 2023)
Type I interferons (IFNs-alpha/beta) are antiviral cytokines that constitute the innate immunity of hosts to fight against viral infections. Recent studies, however, have revealed the pleiotropic functions of IFNs, in addition to their antiviral activities, for the priming of activation and maturation of adaptive immunity. In turn, many viruses have developed various strategies to counteract the IFN response and to evade the host immune system for their benefits. The inefficient innate immunity and delayed adaptive response fail to clear of invading viruses and negatively affect the efficacy of vaccines. A better understanding of evasion strategies will provide opportunities to revert the viral IFN antagonism. Furthermore, IFN antagonism-deficient viruses can be generated by reverse genetics technology. Such viruses can potentially serve as next-generation vaccines that can induce effective and broad-spectrum responses for both innate and adaptive immunities for various pathogens. This review describes the recent advances in developing IFN antagonism-deficient viruses, their immune evasion and attenuated phenotypes in natural host animal species, and future potential as veterinary vaccines.